2019
DOI: 10.1002/slct.201804040
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dots Assisted Synthesis of Gold Nanoparticles and Their Catalytic Activity in 4‐Nitrophenol Reduction

Abstract: A novel biocompatible carbon nanoparticles, i. e., carbon dots (CDs) are prepared from cheap organic precursors and are used to synthesize gold nanoparticles (AuNPs). The formation of CDs are confirmed from their absorption and emission properties. The CDs not only acts as reducing agent but also stabilizes the resulting AuNPs. The high stabilizing effect of CDs can be attributed to their hydrophilic surfaces due to the presence of ‐C=O, ‐OH, etc. functional group as confirmed from FTIR spectral analysis. Basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Furthermore, the converted product, i.e., aromatic amino derivatives can be useful precursor materials for manufacturing various drug molecules and also in making photographic plates (Zhao and Astruc 2015). Moreover, our research group is also actively involved in studying and modulating the catalytic activity of metal nanoparticles through various approaches (Ghosh et al 2019;Mohanta et al 2016;Satapathy et al 2016Satapathy et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the converted product, i.e., aromatic amino derivatives can be useful precursor materials for manufacturing various drug molecules and also in making photographic plates (Zhao and Astruc 2015). Moreover, our research group is also actively involved in studying and modulating the catalytic activity of metal nanoparticles through various approaches (Ghosh et al 2019;Mohanta et al 2016;Satapathy et al 2016Satapathy et al , 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Another weak absorption peak can be observed at around 300 nm, which is ascribed to the n-π* electron transition of hydrophilic groups, mainly CÀ O, C = O, and COÀ H, due to the oxidation state. [32,35] Moreover, the indirect band gap of CNDs was estimated by Tauc's plot by performing the following equation (αhv) 1/2 = B(hv-E g ) , where α is the absorption coefficient, hv is the photon energy (hv = 1240/λ), λ = is the wavelength, B is constant, and E g is the band gap energy. Then by plotting (αhv) 1/2 versus hv as shown in Figure 3b (Inset).…”
Section: Chemistryselectmentioning
confidence: 99%
“…19 Ghosh et al reported a novel approach for synthesis of Au NPs by using CQDs as reducing as well as stabilizing agent, which can enhance catalytic activity towards reduction of PNP. 20 Although nanocomposites have better catalytic properties than NPs, agglomeration occurs during the catalytic process due to their high surface energy, affecting catalytic activity and experimental reproducibility. 21 The newly-fashioned 2D layered inorganic materials, such as silicene, black phosphorus (BP), transition metal oxides (TMOs), graphitic carbon nitride (g-C 3 N 4 ), and MXenes etc., have attracted a lot of attention due to their unique properties and important applications.…”
Section: Introductionmentioning
confidence: 99%
“… 19 Ghosh et al reported a novel approach for synthesis of Au NPs by using CQDs as reducing as well as stabilizing agent, which can enhance catalytic activity towards reduction of PNP. 20 Although nanocomposites have better catalytic properties than NPs, agglomeration occurs during the catalytic process due to their high surface energy, affecting catalytic activity and experimental reproducibility. 21 …”
Section: Introductionmentioning
confidence: 99%